Influence of shear on rheology of the crude oil treated by flow improver - Qun Lei; Fusheng Zhang; Baoshan Guan; Guoliang Liu; Xuening Li; Zhuoyan Zhu (Energy Reports, 2019)
Because the influence of shear on the rheology of waxy crude oil must be considered according to the composition and structure of the waxy crude oil transported via pipeline when a new pipeline is constructed, the risks associated with changes in the waxy crude oil composition during the pipeline operation must be considered in advance. To provide a policy-making basis for designers of new pipelines and managers of existing pipelines, the wax appearance temperature, crude oil components, wax structure and wax crystal morphology were analyzed by differential scanning calorimetry (DSC), gas chromatography (GC), proton nuclear magnetic resonance (1H-NMR) and polarization microscopy. The influence of shear on the rheology of waxy crude oil treated by a flow improver and the relationships among this influence and the waxy crude oil composition, the wax structure and the shear temperature were investigated. The results indicated that above the wax appearance temperature, shear does not affect the rheology of waxy crude oil treated by a flow improver, whereas below the wax appearance temperature, the influence of pipeline shear on the rheology of waxy crude oil is related to the composition of the waxy crude oil and wax structure, which can improve the rheology of certain crude oils but can also deteriorate the rheology of other crude oils. However, pump shear can deteriorate the rheology of crude oil treated by a flow improver. The main reasons for the abovementioned phenomena are that a large number of wax crystals in the crude oil and shear changes the structures of the larger wax crystals formed by eutectic interactions between the flow improver molecules and wax molecules below the wax appearance temperature. In summary, this study provides a reference value for flow improvement research, pipeline design and pipeline management.
Keywords: 330; Crude oil composition; Flow improver; Pipeline shear; Pump shear; Shear temperature; Wax appearance temperature